Pengaruh Kepatuhan Laporan Keuangan, Pemanfaatan Teknologi Informasi, Pengendalian Internal terhadap Pencegahan Fraud Pengelolaan Dana Desa : Studi Empiris pada Pemerintah Desa di Kecamatan Malaka Barat - Valerianus Bria; Fitriana Fitriana; Zaenal Aripin (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
Village fund management in Indonesia still faces serious challenges due to high levels of fraud, including corruption, fraudulent statement, and asset misappropriation. This situation requires more effective prevention systems based on transparency, accountability, and digitalization. This study aims to examine the influence of Financial Reporting Compliance, Information Technology Utilization, and Internal Control on Fraud Prevention in Village Fund Management. The research was conducted in Malaka Barat District using a quantitative approach and Structural Equation Modeling–Partial Least Squares (SEM-PLS). A total of 96 respondents, consisting of village heads and village officials from 12 villages, were selected through purposive sampling, based on their active involvement in managing village funds. The findings reveal that Financial Reporting Compliance and Information Technology Utilization significantly affect Fraud Prevention, while Internal Control does not show a statistically significant effect. Nevertheless, the effect size (f²) indicates that Internal Control contributes moderately at a structural level. These results suggest that reporting practices and digitalization serve as key drivers in building an effective fraud prevention system within village governance. This study contributes theoretically to the development of fraud prevention models in the public sector and offers practical recommendations for village governments to strengthen reporting mechanisms and optimize the use of information technology.